A multidisciplinary investigation on the bioavailability and activity of peptides from lupin protein. (June 2016) - Lammi, Carmen; Aiello, Gilda; Vistoli, Giulio; Zanoni, Chiara; Arnoldi, Anna; Sambuy, Yula; Ferruzza, Simonetta; Ranaldi, Giulia
Highlights: Trans-epithelial transport of lupin peptides investigated in a Caco-2 cell system. Identification of absorbed peptides by HPLC-Chip ESI-MS/MS. Docking of absorbed peptides to HMGCoA reductase by in silico tools. Abstract: Lupin foods provide useful health benefits. Since tryptic and peptic peptides from lupin protein modulate cholesterol metabolism in HepG2 cells and increase LDL-uptake, this work had the goal of assessing whether these lupin peptides are absorbed by human intestinal Caco-2 cells. Cells were differentiated for 15 days and transport experiments were performed by incubating each lupin peptide mixture from the apical side. After 4 h, basolateral solutions were collected and analysed by HPLC-Chip-MS/MS. Eleven tryptic and eight peptic peptides, deriving from lupin storage proteins, were identified in the basolateral samples. An in vitro assay showed that basolateral peptides maintain their capacity to inhibit 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCoAR) activity and in silico docking simulations permitted to hypothesise which peptides may bind more efficiently to the HMGCoAR catalytic site. This is the first investigation providing evidence that lupin peptides with specific structures are potentially absorbed in human intestinal cells.